2011
DOI: 10.1016/j.aca.2011.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Potentiometric flow injection system for determination of reductants using a polymeric membrane permanganate ion-selective electrode based on current-controlled reagent delivery

Abstract: a b s t r a c tA polymeric membrane permanganate-selective electrode has been developed as a current-controlled reagent release system for potentiometric detection of reductants in flow injection analysis. By applying an external current, diffusion of permanganate ions across the polymeric membrane can be controlled precisely. The permanganate ions released at the sample-membrane interface from the inner filling solution of the electrode are consumed by reaction with a reductant in the sample solution thus cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This effect may be due to the fact that the protamine molecules with high molecular weights need a rather long time to cross the membrane [13]. Recently, it has been found that the ion fluxes across the membrane can be modulated and controlled precisely by applying an external current [23,[30][31][32]. Previous reports have shown that ions across the polymeric membrane ion-selective electrode can be selectively and precisely delivered to the sample solution for calibration-free titrations [33].…”
Section: Resultsmentioning
confidence: 99%
“…This effect may be due to the fact that the protamine molecules with high molecular weights need a rather long time to cross the membrane [13]. Recently, it has been found that the ion fluxes across the membrane can be modulated and controlled precisely by applying an external current [23,[30][31][32]. Previous reports have shown that ions across the polymeric membrane ion-selective electrode can be selectively and precisely delivered to the sample solution for calibration-free titrations [33].…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the potential change of the electrode is related to the concentration of the measured substance. Potentiometric analytical methods based on a permanganate release system, for example, have been developed for potentiometric detection of reductants such as dopamine and ascorbate [21,22]. Nevertheless, intense research efforts still focus on their new applications and, herein, ions for the evaluation of the total phenolic content in wine is the emphasis.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, our group has developed an ionophorefree permanganate ISE that utilizes outward ion uxes through the membrane to provide control-released substrates for monitoring the analytes of interest. 16,19 Previous studies have shown that the design based on permanganate release allows a sensitive and reproducible detection of reductants including ascorbate and dopamine. However, the application of this technique is still limited since all reductants that can efficiently react with permanganate ions may produce measured potential interference.…”
Section: Introductionmentioning
confidence: 99%